2017
DOI: 10.18632/oncotarget.15238
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of peripheral regulatory T cells in non-small cell lung cancer patients undergoing radiotherapy

Abstract: BackgroundStudies increasingly focus on the impact of radiotherapy on immunity; however, the role of peripheral cellular immunity prior to radiotherapy in cancer patients remains largely unknown. In this study, we investigated the predictive roles of lymphocyte subsets on tumor progression in non-small cell lung cancer (NSCLC) patients undergoing radiotherapy, and their expression in NSCLC patients at first relapse.MethodsWe enrolled 70 NSCLC patients and 14 age- and sex-matched healthy donors and tested the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…However, CD8+ T cells in cancer patients can lose the expression of CD28 due to the chronic stimulation of tumor antigens and consequently present with a non-responsive status to tumor antigens [28, 29]. We also reported this phenomenon in our previous study, as did other studies, that decreased CD8+CD28+ T cells and increased CD8+CD28− T cells were observable in NSCLC patients when compared with healthy volunteers [3032]. In two recent studies, PD-1 inhibited the function of T cells by inactivating CD28 signaling, and PD-1-targeted therapies rescued CD28+ cells but not CD28− cells among CD8+ T cells, suggesting that CD28 signal plays vital roles in regulating the function of effector T cells [33, 34].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, CD8+ T cells in cancer patients can lose the expression of CD28 due to the chronic stimulation of tumor antigens and consequently present with a non-responsive status to tumor antigens [28, 29]. We also reported this phenomenon in our previous study, as did other studies, that decreased CD8+CD28+ T cells and increased CD8+CD28− T cells were observable in NSCLC patients when compared with healthy volunteers [3032]. In two recent studies, PD-1 inhibited the function of T cells by inactivating CD28 signaling, and PD-1-targeted therapies rescued CD28+ cells but not CD28− cells among CD8+ T cells, suggesting that CD28 signal plays vital roles in regulating the function of effector T cells [33, 34].…”
Section: Introductionsupporting
confidence: 66%
“…The protocol for flow cytometry has been described in our previous study [30]. Four milliliters of fresh blood were collected and stored in EDTA anti-coagulate tubes within 7 days before SABR.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the association between the inflammatory system and tumors. The number of peripheral inflammatory cells before treatment, including lymphocytes, monocytes, and neutrophils, have shown the strong link between the prognosis of different kinds of cancer and the inflammatory system 2232. Neutrophils, reportedly, is an indicator of inflammatory and immune response; their involvement in the proliferation and metastasis of tumor by releasing inflammatory factors, such as neutrophil elastase, matrix metalloproteinase-9, and interleukin-8 has been elucidated 33.…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent study displayed the increased proportions of Treg cells in NSCLC patients, and this may indicate tumor progression. 23 Another study observed that Treg cells, Th17 cells and Treg/Th17 ratio were increased in HCC patients. Treg/Th17 imbalance might serve as an important indicator for determining the progression and prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%